The Oxford shoulder score revisited. - Dawson, J; Rogers, K; Fitzpatrick, R; Carr, A (2009)
The validated, patient-reported Oxford shoulder score (OSS) was introduced around 10 years ago, primarily for the assessment of outcomes of shoulder surgery (excluding shoulder stabilisation) in randomised trials. Its uptake has steadily increased in a number of countries and its use has also been extended. Recently a number of issues have been raised in relation to other related patient-reported outcome measures which were devised around the same time as the OSS. This included recommendations to change the scoring system. This paper reviews issues concerning patient-reported outcome measures that apply to the OSS and makes some recommendations (including changes to the scoring system) as to how it should be used.